MEDICAL AND SOCIAL REHABILITATION OF PATIENTS WITH NARCOTICS ABUSE - Aprilia, Fitriani; Harni, Siti Yuli; Rusli, Siti Nur Fatimah (SYNTIFIC, 2023)
Background. Narcotics are dangerous drugs/substances, which can cause mental dependence on the user, and can cause physical and mental destruction. Narcotics are used in the world of health and is used to anesthetize patients, but many people are wrong using narcotics. Narcotics abuse has recently increased not only among adults but also teenagers and children also abuse it. This research aimed to describe the medical and social rehabilitation of patients with narcotics abuse. Research Method. The research design used a descriptive-analytic approach. PRISMA checklists were used to assess systematic reviews. Databases: ProQuest, CINAHL, Science Direct, Pubmed, and Scopus. Search articles using the PICOS framework. Assessing the risk of study bias can be substituted with the Joanna Briggs Institute (JBI) Critical Appraisal method. Findings. Patient abuse or a person who abuses narcotics is a sick person who is obliged to do so undergoing rehabilitation. Not just using it once but will depend on these haram items even though the law clearly states that you are not allowed to abuse narcotics except for study. Conclusion. An effective way for drug abusers is to rehabilitate those who do narcotics addiction, by rehabilitating narcotics users educated and trained so that in the future they will not fall into the dark world of narcotics again.